2020
DOI: 10.1101/2020.08.24.20175745
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of Venous Thromboembolism in Critically-ill COVID-19 Patients: Systematic Review and Meta-analysis

Abstract: Background: Recent studies revealed a high prevalence of venous thromboembolism (VTE) events in coronavirus disease 2019 (COVID-19) patients, especially in those who are critically ill. Available studies report varying prevalence rates. Hence, the exact prevalence remains uncertain. Moreover, there is an ongoing debate regarding the appropriate dosage of thromboprophylaxis. Methods: We performed a systematic review and proportion meta-analysis following PRISMA guidelines. We searched PubMed and EMBASE for stud… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
2
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 26 publications
2
17
2
3
Order By: Relevance
“…The observation that there is no statistically significant difference in thromboembolism development between patients using warfarin, DOACs, and those not taking therapeutic anticoagulation is in line with some other cohort studies [15,16]. It does not align with the findings of numerous studies conducted in critically-ill patients [14,3739], which found decreased incidence of thromboembolism in patients using therapeutic anticoagulation. This is likely a reflection of the differing severity of illness between study populations.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The observation that there is no statistically significant difference in thromboembolism development between patients using warfarin, DOACs, and those not taking therapeutic anticoagulation is in line with some other cohort studies [15,16]. It does not align with the findings of numerous studies conducted in critically-ill patients [14,3739], which found decreased incidence of thromboembolism in patients using therapeutic anticoagulation. This is likely a reflection of the differing severity of illness between study populations.…”
Section: Discussionsupporting
confidence: 51%
“…Conclusions of research on the impact of anticoagulant therapy on thromboembolism in COVID-19 positive patients has been similarly mixed. Some have found venous thromboembolic risk in critically-ill patients with COVID-19 infection to be significantly higher with prophylactic anticoagulation when compared with therapeutic anticoagulation [14], whereas some retrospective cohort studies have found no statistically significant difference in thrombosis development between groups receiving prophylactic anticoagulation, therapeutic anticoagulation, and intermediate doses [15,16]. However, much of this research is limited to patients admitted to critical care, or studied relatively small populations.…”
Section: Introductionmentioning
confidence: 99%
“…The respiratory symptoms were mild, the chest X‐ray was unremarkable, and she did not develop any thrombotic complications. 17 Despite that, she had severe skin eruption supporting the reported fact that skin rash with SARS‐CoV‐2 has no relation to the severity of the respiratory symptoms. The SARS‐CoV‐2 virus may cause the eruption of guttate psoriasis by a similar mechanism to streptococcal infection by molecular mimicry, or the cytokine excess might cause it during the acute infection.…”
Section: Discussionmentioning
confidence: 82%
“…Thrombosis is a major complication of COVID‐19 infection, and the placenta is not immune. 28 Whether the early ischemic changes in the report are linked to COVID‐19 infection is uncertain and is debatable.…”
Section: Discussion/conclusionmentioning
confidence: 99%